ENTREPRENEUR IN HISTORY EDUCATION CURRICULUM - Aulia Novemy D; Adhitya Rol A; Yunani Yunani (Sriwijaya University Learning and Education International Conference, 2018)
Curricullum is a guide to implementation of education. The vibrant life of the community in various fields is a challenge to the curriculum. One such challenge is to provide space for students to develop an entrepreneurial spirit. Student need to be trained in analyzing and critical history events that have a meaning of entrepreneurship. From historical side, the Indonesian nation has been doing international trading activities sice the time of Srivijaya Kingdom. Before that, the entrepreneurial spirit of Indonesia nation, had appeared i Pre-Literaty period. Historical lesson material containing these entrepreneurial values, the key to succes in the past can be reflection for immediate realization. In addition, it can also create entrepreneurs who have the awareness and adbilitim to develop and preserve the values of local wisdom, through the creation of industry. Through the application of entrepreneurship in the curriculum of history education, student are also trained to change the mindset of student who tihink history is just a fairy tale of the past. alues and entrepreneurial spirit are appropriately studie, and interpreted through historical events.